Guía de práctica clínica para el diagnóstico y tratamiento de la endometriosis sintomática en mujeres en edad reproductiva en el Seguro Social de Salud (EsSalud) - Torres Arones, Esperanza (2024)
Introduction. This article summarizes the clinical practice guideline (CPG) for the diagnosis and treatment of women with symptomatic endometriosis in the Social Security of Peru (EsSalud). Objective. The aim is to offer evidence-based clinical recommendations for diagnosing and managing women with symptomatic endometriosis in EsSalud. Methods. A guideline development group (GEG), consisting of medical specialists and methodologists, was established to create this CPG. The GEG formulated six clinical questions that guided the development of the CPG. Systematic searches of systematic reviews and –where applicable– primary studies were carried out in PubMed and CENTRAL between December 2021 and February 2022. Relevant evidence was selected to address each clinical question. The certainty of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Throughout the CPG development process, the GEG held regular meetings to assess the evidence and formulate recommendations, establish points of good clinical practice, and develop flowcharts. The CPG was formally approved through Resolution No. 62-IETSI-ESSALUD-2022. Results. The CPG addressed six clinical questions, categorized into two primary areas: the diagnosis and management of endometriosis. Based on these questions, eight recommendations were developed, comprising one strong recommendation and seven conditional ones. Additionally, 21 good clinical practice points and two flowcharts were created. Conclusion. This article outlines the methodology and evidence-based conclusions of the CPG for the diagnosis and treatment of women with symptomatic endometriosis in EsSalud.